Technological-digital orality. Pragmatic-communicative study on orality in the audiobook - Cecilia; Gibert, Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper presents a study on the audiobook, a very popular product nowadays, which we propose to analyze from a pragmatic-communicative point of view. This article consists of three parts: in the first one, we will make a summary of orality from its origins to the present day, showing its most relevant characteristics; then, we will dwell on the theory of literary communication and its consequent application in the digital world; and, finally, the audiobook is presented as a new dramatic text..